FENOMENA HIJAB COSPLAY DI MEDIA SOSIAL: ANALISIS SIMULAKRA JEAN BAUDRILLARD - Syadzali, Ahmad; Rahmah, Putri Aulia; Ningsih, Fitria; Khotimah, Husnul (UIN Sumatera Utara Medan, 2026)
This study focuses on the phenomenon of hijab cosplay on social media platforms such as Instagram and TikTok. It aims to understand how Muslim women express themselves through hijab cosplay. This research employs a qualitative method, with data collected through literature review and analysis of social media videos using the hashtag #hijabcosplay. Jean Baudrillard’s theory of simulacra is used as the analytical framework to examine hijab cosplay on social media. The findings indicate that hijab cosplay is a practice that combines the identity of Muslim women who wear the hijab with characters from popular culture, such as anime or manga. This phenomenon is intriguing because it merges two distinct realms: the real world (religious identity) and the imaginary world (fictional characters). Therefore, the phenomenon of hijab cosplay leads into a state of hyperreality, in which the boundaries between reality and simulation become blurred.